2012
DOI: 10.1111/j.1365-2702.2012.04144.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and medication management by the elderly

Abstract: The relationship with nurses in particular is an important issue for the older people. Understanding the factors of adherence and helping people are important areas of research in nursing. The quality of this relationship may be the key to increasing adherence in this group of people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 56 publications
2
90
0
2
Order By: Relevance
“…Consequently, treatments for mental illness are often sought from traditional and spiritual healers to the exclusion of professional mental health services (Aloud & Rathur, 2009) In contrast, the results of the interviews conducted in this study suggest that mental health care provider has both positive and negative role on compliance rate. These results are in agreement with those obtained by Chambers et al (2011) and Henriques, Costa, and Cabrita (2012), who reported a positive impact of health care providers on medication compliance. This is attributed to the fact that this positive role derived from the scientific knowledge being provided by health care professional.…”
Section: Discussionsupporting
confidence: 83%
“…Consequently, treatments for mental illness are often sought from traditional and spiritual healers to the exclusion of professional mental health services (Aloud & Rathur, 2009) In contrast, the results of the interviews conducted in this study suggest that mental health care provider has both positive and negative role on compliance rate. These results are in agreement with those obtained by Chambers et al (2011) and Henriques, Costa, and Cabrita (2012), who reported a positive impact of health care providers on medication compliance. This is attributed to the fact that this positive role derived from the scientific knowledge being provided by health care professional.…”
Section: Discussionsupporting
confidence: 83%
“…Non-adherence to medication is a health phenomenon with a huge impact on the practice, especially in primary care, which affects a large number of the elderly [2,15]. Nowadays, we have an increase in the older age group with all their needs and, every day, nurses are face to face with them.…”
Section: Introductionmentioning
confidence: 99%
“…The primary goal of this study was to identify effective nursing interventions for older people with chronic disease who live at home in the community, able to enhance medication adherence. According to the results of this systematic review, it is not just a matter of adherence, but also an issue of management of the medication prescribed [2,8,21,23]. In this systematic review we found evidence of effective interventions that should be replicated and re-tested in different target population, with the aim to promote well-being in older people, helping them to live with dignity and autonomy.…”
mentioning
confidence: 99%
See 2 more Smart Citations